The Effect Of Self-Help Group Therapy On Symptoms Of Attention Disorder In Adolescents - Sefira Khoirotus Salsa; Muhammad Ari Arfianto; Ajeng Pramudianingtyas; Amelia Wulan Sari; Setia Purbaningrum; Rafika Azzahra Salsabila Utomo (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Attention disorders often hinder students' mental well-being, social relationships, and academic achievement. One effective intervention to address these symptoms is Self-Help Group (SHG) therapy, emphasizing peer support and emotional regulation. This quantitative study used a one-group pre-posttest pre-experimental design involving 76 junior high school students in Malang Regency. The intervention was carried out in 4 SHG sessions conducted across 17 meetings aimed at improving concentration and coping skills. Attention deficit symptoms were measured using the Pediatric Symptom Checklist-17 (PSC-17) scale and analyzed using the Wilcoxon Signed Rank Test. The results showed that the average attention deficit score decreased from 5.92 (SD = 1.83) before the intervention to 5.41 (SD = 2.26) after the intervention, indicating an improvement in focus and attention. Statistical analysis showed a significant effect with a p-value of 0.011 (p 0.05). These findings prove that SHG therapy is effective in reducing attention deficit symptoms and improving students' learning focus. The application of SHG in schools can be an innovative psychosocial approach to support mental health and education quality in Indonesia.